Can sharing economy mode advance the transition of China's energy sector effectively: A case of PV technology transition?. (November 2021) - Hou, Jianchao; Wang, Min; Liu, Pingkuo
Abstract: Driven by the development of global Energy Internet and the requirement of energy transition, the sharing economy mode in energy sector has turned into a novel inspiration. This paper aims to explore whether the sharing economy model advance China's energy transition effectively. We describe the system of Energy with Uber-like mode, and introduce the Uber-like Mode into the PV power sector. By using the Analytic Network Process method, a set of comprehensive benefit evaluation system for the Uber-like mode plus renewables project is put forward from aspects of the technical and economic benefit, the social and environmental benefit, the energy benefit and the safety (reliability) benefit. The Uber-like mode plus PV project, as one specific application, is chosen as a case study to verify the effectiveness of the evaluation model. Based on the evaluation results, SWOT is adopted to discuss the internal conditions and the external environment for Renewables Sharing Economy in China. Finally, this article puts forward a series of suggestions to realize the goal of the proper adjustment of energy structure with respect to the renewables' sharing economy mode.